Library architecture: noise controlling - Karunanayaka, K.G.D.A (My University, 2012)
The article deals with the evaluation of internal noise controlling strategies implemented in university libraries in Sri Lanka with special reference to Colombo, Kelaniya and Sri Jayawardanapura. The noise controlling is a very important factor in effective user services. The study found that the noise creation could he arisen due to the materials used in interior fabrication and as well as by reader behaviors. Therefore the possible noise disturbances could be avoided through proper planning of interior designing for a user expected noise less library